2019
DOI: 10.14569/ijacsa.2019.0100785
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Analysis in Bank Direct Marketing Prediction

Abstract: Gaining the most benefits out of a certain data set is a difficult task because it requires an in-depth investigation into its different features and their corresponding values. This task is usually achieved by presenting data in a visual format to reveal hidden patterns. In this study, several visualization techniques are applied to a bank's direct marketing data set. The data set obtained from the UCI machine learning repository website is imbalanced. Thus, some oversampling methods are used to enhance the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Singh et al [38] compared the performance of LR, SVM, RF, and DT models for the prediction task and suggested that the RF model achieved the best result. A similar study by Hou et al [39] compared the performance of NB, DT, RF, SVM, and NN and concluded that RF achieved the highest accuracy while NN produced the highest sensitivity value, suggesting its robustness in the prediction task. However, they did not explicitly use any feature selection or class balancing technique.…”
Section: Feature Selectionmentioning
confidence: 88%
“…Singh et al [38] compared the performance of LR, SVM, RF, and DT models for the prediction task and suggested that the RF model achieved the best result. A similar study by Hou et al [39] compared the performance of NB, DT, RF, SVM, and NN and concluded that RF achieved the highest accuracy while NN produced the highest sensitivity value, suggesting its robustness in the prediction task. However, they did not explicitly use any feature selection or class balancing technique.…”
Section: Feature Selectionmentioning
confidence: 88%
“…(9): (9) where density is inversely proportional to the sparsity hence, inverse of density will be equal to the sparsity factor that can be measured as Eq. (9): (10) After measuring sparsity for each filtered minority cluster, we can take sum of all the sparsity measures and this sparsity sum is then transformed into the sampling weights as Eq. (11):…”
Section: Synthetic Instance Generationmentioning
confidence: 99%
“…At present, data mining tasks involve large amount of data which is complex and embedded with noise; hence techniques used for information extraction are needed to be efficient and effective decisions making [1] [2]. In data mining, classification is the most commonly performed data analysis task in realworld applications including medical, engineering, and business [3][4] [5]; i.e., cancer prediction [6], face detection [7], software fault detection [8] [9], bankruptcy prediction [10] [11], fraud detection [12]. Majority of classification algorithms consider that the given dataset has the proportional instances among the classes, and these algorithms are not intelligent enough to detect the inappropriate distribution of instances.…”
Section: Introductionmentioning
confidence: 99%